MENINGKATKAN MINAT DAN PEMAHAMAN PELAJAR SMP TERHADAP BUDAYA MELALUI PENTAS SENI VIRTUAL - Gregorio A M Kanaf; Divina Ayudia Genevieve; Siprianus Soleman Senda (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The Covid-19 pandemic that has attacked the world has had a major impact in various fields of life. Two areas of life affected by the Covid-19 pandemic are education and culture. The reduced quality of learning, reduced creativity and interest in the arts are proof that the pandemic has had a major impact. Thus, it is necessary to increase students' passion and interest in education and culture. One of the efforts made is by holding virtual art performances. This research aims to see and analyze the extent to which virtual art performances play a role in increasing the interest of Santo Yoseph Catholic Junior High School students in NTT culture. The research method used is qualitative research method. By using this method, researchers conducted observations and interviews to collect data. As a result, the researcher found that students' interest and understanding of art and culture has increased. Students not only perform dances or songs from a region, but they are able to understand well what has been displayed.